Analysis of the effects of different provocative methods on bioelectrical brain activity in patients with epilepsy - Seniut , G.; Streckytė , D.; Mameniškienė , R. (Neurologijos seminarai, 2019)
ntroduction. The sensitivity of EEG is increased by performing standard provocative tests. The effects of additional cognitive tasks on bioelectrical brain activity aren’t widely studied. We aim to mine the effects of cognitive tasks in patients with epilepsy. Methods. EEGs of 144 patients with epilepsy were registered (age 37.9±16.2; 52.8% – women; 66.7% had focal epilepsy) using 3 standard (HV, IPS, eyes closed-eyes open) and 4 additional tests (reading aloud in a native and unknown language, solving a Rubik’s cube, crossing out letters). Interictal and ictal EDs were evaluated. Results. Eyes closed-eyes open test provoked EDs in 9.7% of EEGs, an inhibitory effect was registered in 34.7%. HV provoked EDs in 52.1% of patients, a seizure in one patient with focal epilepsy, inhibited EDs in 5.6% of patients, most of them had generalized epilepsy (p=0.005). EDs during IPS were registered in 16.7% of EEGs, in one patient with focal epilepsy – a seizure, inhibition was found in 32.6%. Reading in an unknown language provoked EDs in 9.7%, inhibited – in 41%, more so in those with generalized epilepsy (p=0.003). Reading in a native language provoked EDs in 9.7%, inhibited – in 40.3%, especially in patients with generalized epilepsy (p=0.027). Solving a Rubik’s cube and crossing out letters provoked EDs in respectively 15.3% and 11.1%, inhibited them in 29.9% and 34%, both did so more in patients with generalized epilepsy (p=0.017; p=0.014). Conclusions. Most frequently EDs were provoked by hyperventilation, whereas cognitive tasks inhibited them, more so in patients with generalized epilepsy. Patients with generalized epilepsy were also more responsive to IPS. Reading in a native language most frequently inhibited EDs in patients with focal epilepsy and reading in an unknown language had the same effect on patients with generalized epilepsy.